2010
DOI: 10.1016/j.rbmo.2010.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in diminished ovarian reserve after dehydroepiandrosterone supplementation

Abstract: Dehydroepiandrosterone (DHEA) has been reported to improve oocyte/embryo yields and oocyte/embryo quality in women with diminished ovarian reserve. Whether DHEA objectively improves ovarian reserve is, however, unknown. This study investigated 120 consecutive patients with diminished ovarian reserve, supplemented for 30-120 days (mean 73+/-27) with DHEA (25mg three times daily). Anti-Müllerian hormone (AMH) concentrations were determined in relationship to DHEA supplementation using linear regression and, long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 34 publications
3
58
2
4
Order By: Relevance
“…By IVF cycle start, however, only AMH was left significantly associated with pregnancy chances (Fig. 2a), which correlates well with the earlier reported observations that AMH, but not FSH improves with DHEA supplementation, and that increases in AMH levels are associated with improved pregnancy chances with IVF [21].…”
Section: Fsh Bl/cs Amh Bl/cs Fsh/androgen and Amh/androgen Ratiossupporting
confidence: 91%
“…By IVF cycle start, however, only AMH was left significantly associated with pregnancy chances (Fig. 2a), which correlates well with the earlier reported observations that AMH, but not FSH improves with DHEA supplementation, and that increases in AMH levels are associated with improved pregnancy chances with IVF [21].…”
Section: Fsh Bl/cs Amh Bl/cs Fsh/androgen and Amh/androgen Ratiossupporting
confidence: 91%
“…6a) [15,17,23]. Six trials including 163 patients that studied women older than 36 also indicated increased oocyte numbers after DHEA treatment (WMD 1.31, [13] Ca se-control None None N/A Intention to treat analysis *** * ** Barad [12] Prospective cohort study None None N/A Intention to treat analysis *** * ** Sonmezer [23] Prospective cohort study None None N/A Intention to treat analysis *** * ** Gleicher [32] Case-control None None N/A Intention to treat analysis *** * ** Wiser [14] RC T Artini [33] RC T Moawad [24] RCT Fusi [25] Prospective cohort study None None N/A Intention to treat analysis *** * ** Hyman [26] Prospective cohort study None None N/A Intention to treat analysis ** * ** Singh [27] Prospective cohort study None None N/A Intention to treat analysis ** * ** Yeung [32] RCT Yilmaz [36] Prospective cohort study None None N/A Intention to treat analysis *** * ** Jirge [15] Prospective cohort study None None N/A Intention to treat analysis *** * ** Kara [28] R C T Vlahos [2] Prospective cohort study None None N/A Intention to treat analysis **** * ** Xu [16] C a s e -control None None N/A Intention to treat analysis ** * ** Yeung [6] R C T Zangmo [17] Prospective cohort study None None N/A Intention to treat analysis ** * ** Zhang [29] RCT Tartagni [30] RCT Tsui [31] Prospective cohort study None None N/A Intention to treat analysis *** * ** Fig. 6b) [12,14,17,25,26,31].…”
Section: Oocyte Numbersmentioning
confidence: 99%
“…We also compared the results from case-control trials. Of nine such trials, we selected five (total 280 patients) and discarded four when controlling for age, DHEA treatment time, follicle-stimulating hormone (FSH), and luteinizing hormone (LH) doses for COH [2, 14,16,33,34]. This analysis also indicated a larger retrieved oocyte number after DHEA treatment (WMD 0.27, 95 % CI 0.12-0.42, p = 0.0004, I 2 = 49 %, Fig.…”
Section: Oocyte Numbersmentioning
confidence: 99%
“…DHEA supplementation is usually oral and administered at 25 mg, three times a day, or 75-90 mg for the entire day, for 6 to 24 weeks. A previous casecontrol study showed that DHEA improved ovarian reserve and that it significantly increased antral follicle counts (AFCs), anti-Müllerian hormone (AMH) levels (32)(33)(34), numbers of fertilized oocytes, normal day 3 embryos, embryos transferred, and the average embryo score per oocyte (35) while significantly decreasing day 3 follicle-stimulating hormone (FSH) (33), fertilized aneuploid embryos (36), and miscarriage rates (37) (all p-values < 0.05). Estradiol (E2) levels tripled according to two studies (12,38) but decreased according to a third (34).…”
Section: The Effects Of Dhea Supplementation In Women With Dormentioning
confidence: 99%